2022
DOI: 10.1017/cjn.2022.65
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging Abnormalities in Mixed Alzheimer’s and Subcortical Vascular Dementia

Abstract: Background: A large proportion of Alzheimer’s disease (AD) patients have coexisting subcortical vascular dementia (SVaD), a condition referred to as mixed dementia (MixD). Brain imaging features of MixD presumably include those of cerebrovascular disease and AD pathology, but are difficult to characterize due to their heterogeneity. Objective: To perform an exploratory analysis of conventional and non-conventional structural magnetic resonance imaging (MRI) abnormalities in MixD and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
(134 reference statements)
1
3
0
Order By: Relevance
“…Considering an exhaustive set of neuropathologies, we found a significant association between cerebrovascular and tau pathology severity with WMH burden. This supports the previously reported link between AD and WMHs independently of comorbid vascular pathology [259][260][261].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering an exhaustive set of neuropathologies, we found a significant association between cerebrovascular and tau pathology severity with WMH burden. This supports the previously reported link between AD and WMHs independently of comorbid vascular pathology [259][260][261].…”
Section: Discussionsupporting
confidence: 92%
“…AD neuropathology, as well as disease severity in patients presenting it, are also associated with WMH burden [259]. This relation cannot be explained solely by comorbid vascular disease, as higher WMH volumes have been found in individuals with clinically-defined mixed AD and VaD compared to patients presenting only one of the two [260]. Exploring the separate effects of AD hallmarks on WMHs, some studies found these lesions are associated with amyloid-β but not to tau [261][262][263], while others reported the opposite [264,265].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with mixed AD and vascular pathologies show greater levels of white matter hyperintensities and more advanced white matter degeneration on structural MRI and DWI relative to those with AD only or vascular cognitive impairment only. 62 Mixed dementia cases have also been shown to have more rapid degeneration in motor function, such as gait and grip strength. 63 Cerebrovascular risk factors in both cognitively impaired patients and cognitively normal patients provide additive risk for cognitive decline, although this may vary by ethnicity, as well as more prominent perivascular spaces and white matter hyperintensities on MRI.…”
Section: Comorbidity Of Cerebrovascular Disease With Other Dementia P...mentioning
confidence: 99%
“…At this time, only AD and vascular pathologies can be visualized in vivo, because other notable pathologies (eg, α-synuclein, TDP-43, fused in sarcoma [FUS]) can be assessed only at autopsy. Patients with mixed AD and vascular pathologies show greater levels of white matter hyperintensities and more advanced white matter degeneration on structural MRI and DWI relative to those with AD only or vascular cognitive impairment only 62 . Mixed dementia cases have also been shown to have more rapid degeneration in motor function, such as gait and grip strength 63 .…”
Section: Comorbidity Of Cerebrovascular Disease With Other Dementia P...mentioning
confidence: 99%